Understanding the planning process and challenges in Shariah audit execution: the case of Malaysian takaful operators - Abdullah, Nurdianawati Irwani; Shafii, Zurina; Mohamad Puad, Noor Aimi (2019)
This study conducts a cross-sectional, case-based field study comparing the planning processes in Shariah audit for three takaful operators in Malaysia. A case study is an empirical enquiry to investigate facts in their context, and states that its unique strength is its ability to deal with various pieces of evidence (documents and interviews), and to detect missing constructs (Yin, 2003). Three takaful operators were selected in this study. The backgrounds and characteristics of the takaful were shown in Figure 3.0. These three takaful companies were selected because of their similarities as they also provide conventional insurance services. Hence, the comparison can be made whether they are doing a separate audit for takaful or they just conduct the audit at the group level.